The prediction of adult attachment orientation from perceived maternal and paternal parenting characteristics - Parcon, Apryl Mae C. (Philippine Journal of Psychology, 2011)
"The study aimed to know which perceived parenting characteristics predict adult attachment orientations. It validated the importance of both mothers' and fathers' parenting characteristics in influencing attachment orientations."